Breastfeeding support in low and middle-income countries: Secondary analysis of national survey data. (March 2020) - Peven, Kimberly; Purssell, Edward; Taylor, Cath; Bick, Debra; Lopez, Velma K.
Abstract: Background: Early initiation of breastfeeding and exclusive breastfeeding can reduce infant mortality. Breastfeeding support interventions such as counselling may improve adherence to recommended practices. However, it is not known if these interventions work at the population level. Objective: The aim of this study was to assess the relationship between early postnatal breastfeeding support and recommended breastfeeding practices. Design/setting: We pooled data from 11 Demographic and Health Surveys in Africa ( n  = 7), South East Asia ( n  = 2), the Americas ( n  = 1), and Europe ( n  = 1) to analyse these associations at the population level. Participants: We limited the data to the most recent live births in the two years before the survey, including 41, 431 births. Analysis: We fitted three multivariable logistic regression models to estimate the relationship between early postnatal breastfeeding support (a newborn postnatal check within an hour of birth plus counselling and observation of breastfeeding within two days) and three breastfeeding outcomes (early initiation of breastfeeding, absence of prelacteal feeding, and exclusive breastfeeding), adjusting for sociodemographic characteristics and birth-related factors. Findings: Early breastfeeding support was associated with a 24% increase (OR=1.24 95%CI=1.11, 1.39) in the odds of initiating breastfeeding within one hour of birth. No relationships were found between breastfeeding support and prelacteal feeding in the first three days or exclusive breastfeeding at six months. Key conclusion: While postnatal breastfeeding counselling and observation may improve early initiation of breastfeeding, impact is not persistent for longer term breastfeeding outcomes. Implication for practice: Improved training for breastfeeding support and an enabling policy environment are required to improve breastfeeding practices for women and newborns.